RETERRITORIALIZING CHINESE LIVING SPACE APARTMENTS IN SINGAPORE - de Yong, Sherly (Institute of Research and Community Outreach - Petra Christian University, 2011)
A home can be more than just a house or a place to live in. A home is a place where a person can express his feelings privately (personal) and socially (public). As in Chinese traditional houses, a home can give a concrete form of significant ethical relations between the horizontal hierarchy (within the family) and vertical hierarchy (with God). The shape of the traditional Chinese house has a unique arrangement of space. The house has a wall to protect them from intruders and bad conditions. The family’s ancestor altar in the main hall which is connected to the bedrooms reveal the relationship of the family, and the courtyard represents a space to show their relationship with God. The arrangement of the living spaces show how they were reterritorializing their private and public spaces. Due to the flocking of population in Singapore, lack of space and modernity, the Chinese Singaporeans are rapidly replacing one-story traditional homes to multi-leveled apartments. Old and big extended family patterns like in the traditional Chinese houses are no longer present. They are breaking up the family into separate living units and reterritorializing their private and public space. Reterritorializing means migrating their previous territory of space and making a new territory in the new place. The examples of this phenomenon of reterritorializing of space is: putting God’s worship outside their apartment’s door or the corridor and putting the service area (kitchen) that used to be in the private area to the public area of the house.